Nonlinear Hybrid Controller for a Quadrotor Based on Sliding Mode and Backstepping - Chuan Lian Zhang; Kil To Chong (IAES International Journal of Robotics and Automation (IJRA), 2015)
In this paper, one nonlinear hybrid controller, based on backstepping and sliding mode, was developed and applied to a quadrotor for waypoint navigation application. After dynamics modeling, the whole quadrotor dynamics system could be divided into two subsystems: rotational system and translational system. Backstepping control law was derived for attitude control whereas sliding mode control law was developed for position control. By using Lyapunov theory and satisfying sliding stable rules, the convergence of system could be guaranteed. A nonlinear equation was proposed to solve the under-actuated problem. To validate the effectiveness of proposed nonlinear hybrid controller, waypoint navigation simulation was performed on the nonlinear hybrid controller. Results showed that the nonlinear hybrid controller finished waypoint navigation successfully.